Foam rolling as a recovery tool following an intense bout of physical activity - MacDonald, G.; Button, D. C.; Drinkwater, E. J.; Behm, D. G. (Medicine & Science in Sports & Exercise, 2014)
PURPOSE: The objective of this study is to understand the effectiveness of foam rolling (FR) as a recovery tool after exercise-induced muscle damage, analyzing thigh girth, muscle soreness, range of motion (ROM), evoked and voluntary contractile properties, vertical jump, perceived pain while FR, and force placed on the foam roller. METHODS: Twenty male subjects (=3 yr of strength training experience) were randomly assigned into the control (n = 10) or FR (n = 10) group. All the subjects followed the same testing protocol. The subjects participated in five testing sessions: 1) orientation and one-repetition maximum back squat, 2) pretest measurements, 10 × 10 squat protocol, and POST-0 (posttest 0) measurements, along with measurements at 3) POST-24, 4) POST-48, and 5) POST-72. The only between-group difference was that the FR group performed a 20-min FR exercise protocol at the end of each testing session (POST-0, POST-24, and POST-48). RESULTS: FR substantially reduced muscle soreness at all time points while substantially improving ROM. FR negatively affected evoked contractile properties with the exception of half relaxation time and electromechanical delay (EMD), with FR substantially improving EMD. Voluntary contractile properties showed no substantial between-group differences for all measurements besides voluntary muscle activation and vertical jump, with FR substantially improving muscle activation at all time points and vertical jump at POST-48. When performing the five FR exercises, measurements of the subjects' force placed on the foam roller and perceived pain while FR ranged between 26 and 46 kg (32%-55% body weight) and 2.5 and 7.5 points, respectively. CONCLUSION: The most important findings of the present study were that FR was beneficial in attenuating muscle soreness while improving vertical jump height, muscle activation, and passive and dynamic ROM in comparison with control. FR negatively affected several evoked contractile properties of the muscle, except for half relaxation time and EMD, indicating that FR benefits are primarily accrued through neural responses and connective tissue.